The Influence of Third-party Funds; Asset Quality, Profit, and Lost Sharing to The Islamic Bank Liquidity in Indonesia - Maulida Berniz, Yulis; Najmudin, Najmudin; Jayanti, Esih; Yustina Rahmawati, Ika; Utami, Yuni (Publisher Cv. Inara, 2023)
During the COVID-19 pandemic, Islamic commercial banks experienced liquidity excess due to the third-party funds that increased and the weak distribution of financing by Islamic banks. In addition, the asset quality of Islamic banks is showing good development, this will affect the bank's ability to meet sufficient liquidity. This study uses 7 Islamic commercial banks as a sample from a population of 14 Islamic commercial banks registered in the Financial Services Authority (OJK) from March 2012 to December 2020 (quarterly data) period. This research method uses a fixed-effect model, with a GLS weight approach, Cross-section SUR. The results of this study are third party funds, asset quality (Non-Performing Financing), and Capital Adequacy Ratio have a significant effect on the liquidity of Islamic banks, while Profit and Loss Sharing and Return on Assets do not affect the liquidity of Islamic banks.